DEVELOPMENTAL DELAY AND MENTAL RETARDATION IN PATIENTS WITH INHERITED METABOLIC DISORDERS - RAMADEVI.K; P.THIRUMALAIKOLUNDUSUBRAMANIAN (International Journal of Pharma and Bio Sciences, 2016)
Developmental delay and Mental retardation commonly refer to decreased intellectual and functional abilities and are associated with a wide spectrum of disorders. Identification of the condition is very important because it has implications regarding treatment (in potentially treatable disorders), prognosis, genetic counseling of families, and implementation of prevention programs.